Potensi Peningkatan Penyerapan Karbon Melalui Sistem Tanaman Sela Berbasis Karet - Sahuri, Sahuri (Bumi Lestari; Vol 18 No 1 (2018)DO - 10.24843/blje.2018.v18.i01.p05, 2018)
Rubber tree (Hevea brasilliensis) has a very big role in the economy and the absorption of CO 2 . Rubber plants as well as forest plants capable of processing CO 2 as a carbon source that is used for photosynthesis. CO 2 absorption can be enhanced through the implementation of rubber based intercrops system. This study aims to determine the potential for carbon sequestration in rubber based intercrops system. The experiment was conducted at the Sembawa Research Station, South Sumatra, with two cropping pattern (PT), namely PT1: rubber plants + intercrops (peneaple, cowpea, sweet sorghum, upland rice, sweet corn, ginseng), and PT2: rubber plant of monocultures. Measurement of carbon reserves consist of tree biomass, intercrops biomass and soil organic matter. The results showed that the absorption CO 2 of intercrops i.e: peneaple  (5,87 tons/ha), cowpea (4,08 tons/ha), sweet sorghum (12,84 tons/ha), upland rice (8,68 tons/ha), sweet corn (10,63 tons/ha), and ginseng (3,31 tons/ha). The addition of carbon sequestration  due to intercrops rubber were 296,59% or 33,96 tons CO 2 /ha compared to the rubber plant of monocultures.